The use of macroalgae (Gracilaria changii) as bio-adsorbent for Copper (II) removal - Lavania-Baloo (Institute of Physics Publishing, 2017)
Biosorption of heavy metals using marine macroalgae biomass can be an effective process and alternative to conventional methods. Activated carbon was developed from macroalgae (Gracilaria changii) and used as adsorbents for the removal of copper (II) from wastewater. Gracilaria changii based activated carbon (GCBAC) was prepared using muffle furnace at a constant temperature of 300 °C for 1 hour. Batch adsorption experiments were conducted to investigate the effets of important parameters such as pH, contact time, initial metal concentration and adsorbent dosage on the removal of Cu (II) from synthetic aqueous solution. Batch adsorption study shows that removal of Cu (II) using GCBAC relied upon pH, contact time, initial metal concentration and GCBAC dosage. The optimum conditions parameters were found to be pH 6.0, time of 60 minutes and GCBAC dosage of 0.3 g, respectively. Adsorption data was described better by Freundlich isotherm model with R2 value of 0.7936. The maximum Cu (II) adsorption capacity of GCBAC was found to be 0.07 mg/g. The experimental adsorption data obtained fitted well into Pseudo-second-order kinetic model, with R2 value near unity. Thus, GCBAC can be used as an effective adsorbent for the removal of Cu (II) from aqueous solution. © Published under licence by IOP Publishing Ltd.